Perbandingan Polaritas VV dan VH dalam Penerapan Algoritma NDFI pada Pemetaan Banjir Kota Palembang - Az-zahra, Maudhy; Handayani, Ade Silvia; Lindawati, Lindawati (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Frequent floods in Indonesia, particularly in Palembang, South Sumatra, pose significant economic and social challenges due to land-use alterations, river overflow, and intense precipitation. The region's geographical, geological, and demographic features, compounded by global climate change, worsen the situation. Flood mapping and monitoring, utilizing satellites like Sentinel-1 with Synthetic Aperture Radar (SAR), are pivotal for mitigating these disasters. Sentinel-1's SAR technology aids wetland monitoring, acting as a natural water absorber and minimizing flood risks. Data from Sentinel-1, especially in VV and VH polarizations, offer profound insights into hydrological systems influencing floods. SAR efficiently comprehends Earth's environment, facilitating high-precision and rapid flood mapping using the NDFI method in Palembang. This study compares VV and VH polarizations in the NDFI algorithm to identify the most suitable polarization for accurate flood mapping. Results show VV data achieves 97.8% mapping accuracy compared to VH's 50%. The high accuracy of VV data signifies superior flood area detection. Moreover, VV's sigma0 value (backscatter) at -1.47 dB exceeds VH's approximately -20.47 dB, indicating stronger signal intensity. Hence, VV-polarized data, considering its performance, proves more effective for flood mapping.   Keywords: NDFI; Flood; Polarization; Sentinel